Preparation, quality evaluation and storage stability of peach-soy fruit leather - Anju, B; Kumari, KR; Anand, V; Anjum, MA (SAARC Journal of Agriculture, 2014)
The peach-soy leather was prepared from different blends of peach pulp and soy-slurry. The peach pulp and soybean slurry were blended in the ratios of 100:0, 95:5, 90:10, 85:15, 80:20, 75:25 and 70:30. The prepared leather was stored for a period of four months to ascertain changes in physico-chemical and sensory characteristics. The analysis of leather revealed significant differences among different blends. Highest moisture content i.e. 21.99 percent was recorded in B1 (100:0:: P:S). The highest TSS and acidity of 12.05 degree Brix and 2.77 percent were recorded in B1 (100:0:: P:S), respectively, whereas the highest reducing sugar and total sugar contents of 30.16 and 60.41 percent were found in B1 (100:0:: P:S), respectively. The highest protein and fat contents were recorded in B7 (70:30:: P:S), whereas ascorbic acid content was the highest (23.54 mg 100g-1) in B7 (70:30:: P:S). Sensory evaluation of leather revealed that the highest score of 8.14 was recorded in B4 (85:15:: P:S) and lowest score of 5.63 was recorded in B7 (70:30::P:S). In general there was an increase in TSS, acidity and sugars and decrease in protein, fat and ascorbic acid contents and all sensory attributes during four months storage in different blends of leather. DOI: http://dx.doi.org/10.3329/sja.v12i1.21114 SAARC J. Agri., 12(1): 73-88 (2014)